Impact of Regular Sleep Patterns on Learning Achievement in Preschool Children in Mindahan Batealit: Issues and Implications - Purnama, Helmi Sintha Faradila; Zulfahmi, Muhammad Nofan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Regular sleep patterns are one of the crucial factors that can affect children's development, including in terms of learning achievement. At preschool age, children are at a very important stage of development, where they experience significant physical, cognitive, and emotional growth. The study aimed to examine the sleep patterns of preschool-aged children in Dukuh Mindahan Lor Batealit Jepara. Research was limited to Dukuh Mindahan Lor Batealit Jepara. The subjects of the study were preschool-age children in Dukuh Mindahan Lor Batealit Jepara and the object in this study was the sleep patterns of preschool-age children in Dukuh Mindahan Lor Batealit Jepara. This study uses qualitative research methods to obtain an in-depth description of the sleep patterns of preschool children, with a case study approach using information collection techniques in the form of interviews, observations and documentation in analyzing and describing the sleep patterns of preschool children in Mindahan Lor village. The results of this study show that the results of this study show a positive correlation between optimal sleep duration (9-10 hours per night) and learning achievement of preschoolers. Children who get enough sleep tend to have higher cognitive scores and show better concentration skills in class.